IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT (SBM) IN EXEMPLARY PUBLIC SENIOR HIGH SCHOOLS, TUNAS BANGSA AND 1ST PUBLIC SENIOR HIGH SCHOOL IN ACEH BARAT DAYA DISTRICT TO IMPROVE EDUCATIONAL QUALITY - Fengki Yuhadi; Hizir; Niswanto (CV. RADJA PUBLIKA, 2024)
The concept of quality management has developed significantly in both the industrial and educational sectors. In education, one of the quality management concepts is School-Based Management (SBM). The purpose of this study is to determine: (1) The implementation of programs for autonomy, partnerships, participation, transparency, and accountability; (2) Support and obstacles in the implementation of School-Based Management (SBM); and (3) Internal/external interventions in the implementation of School-Based Management (SBM) at Tunas Bangsa Exemplary Public Senior High School and 1st Public Senior High School in Aceh Barat Daya District. Data collection techniques include: observation, interviews, and documentary studies. The research subjects include school principals, educators, education personnel, and school committees. Data analysis uses a quantitative approach to draw conclusions from the percentage results of the research and a qualitative approach starting from data reduction, data presentation, and drawing conclusions. The results of the study are: (1) The implementation of the School-Based Management (SBM) program at Tunas Bangsa Exemplary Public Senior High School and 1st Public Senior High School in Aceh Barat Daya District has been carried out well, but efforts are still being made to further improve the quality of education. There are five basic principles implemented in School-Based Management: autonomy, partnerships, participation, transparency, and accountability. (2) Factors supporting the implementation of School-Based Management (SBM) at Tunas Bangsa Exemplary Public Senior High School and 1st Public Senior High School in Aceh Barat Daya District are the leadership of the principal that is capable, effective, and efficient, support from parents and the community, the performance of teachers and school staff, and government support. The inhibiting factors are the still limited understanding of school members and related parties regarding the implementation of SBM as well as communication and coordination that still need to be built. (3) There are no internal or external interventions in the implementation of SBM at Tunas Bangsa Exemplary Public Senior High School and 1st Public Senior High School in Aceh Barat Daya District. Efforts that can be made by the principal to minimize interventions include more frequent socialization of community participation in education, and deepening management knowledge by sending teachers to attend trainings.